Mechanical strength characterization of recovered azobé timber boards for reuse - Abhijith Kamath; Ganesh Shri Raam Kalaichelvi Senthil Kumar; Geert Ravenshorst; Jan-willem van de Kuilen (Case Studies in Construction Materials)
Hundreds of kilometers of timber sheet piles protecting the banks of canals of the Netherlands are nearing the end of their service life and need to be replaced. Even though azobé wood is very widely used, little is known about the current state of the azobé timber sheet piles that have been in service for many decades. More information about the current strength is necessary for planning any intervention, maintenance or reuse of the recovered sheet pile boards. This study aims to characterize the current state of azobé sheet piles using destructive techniques such as four point bending tests, compression tests and non-destructive techniques such as micro-drilling and visual assessment. To achieve this objective sheet piles that were in service for over 57 years were pulled out and tested in the laboratory. The non-destructive tests results indicate that the deterioration of azobé sheet piles is concentrated on the superficial layers of the boards. Visual classification and micro drilling techniques did not yield results that support the findings from the destructive tests. The bending strength and modulus of elasticity of in service sheet piles used in current study was found to be lower by about 25 % and 30 % respectively when compared to new azobé sheet piles reported in literature. Based on average values of measured dimensions, density of the sheet piles in this study was in general, lower compared to new sheet piles. Thus, the lower strength could be due to deterioration, lower intrinsic quality of the recovered sheet piles, or simply fall within the natural scatter of the material. In addition an exercise to classify the samples to a strength class is shown for practicing engineers.